Chemical Clogging of Emitters and Evaluation of Their Suitability for Saline Water Drip Irrigation†. (2nd June 2016) - Lili, Zhangzhong; Yang, Peiling; Ren, Shumei; Li, Yunkai; Liu, Yu; Xia, Yuhong
Abstract: Drip irrigation with saline water is one of the most effective methods to ease the current worldwide water shortage. However, there are more ionic compositions in saline water, resulting in easy clogging of drip irrigation emitters. In this study, we selected five common emitters as study subjects and conducted a saline water drip irrigation experiment in the Hetao Irrigation District (Inner Mongolia, China). The results showed that, as the running time increased, the discharge ratio variation (Dra) and coefficient of uniformity (CU) both declined. The Dra and CU of cylindrical emitters decreased gently, while those of flat emitters showed a 'slow–fast' downward trend. The Dra of the five different emitters decreased to 46.3–78.6% and the CU dropped to 23.5–85.0% over the course of the experiment. Cylindrical emitters with higher flow showed better anti‐clogging capacity. The temporal and spatial distribution of clogging materials within emitters differed. Specifically, the dry weights (DW) of clogging materials in different positions occurred in the order of DWhead < DWmiddle < DWend laterally, and clogging materials accumulated gradually with time. The average clogging materials distribution density showed a significant negative linear relationship with Dra and CU ( R 2 = 0.81 and 0.88). It indicated that as the clogging materials accumulated, the anti‐clogging capacity of emitters degraded. The chemical constituents of the clogging materials in the different emitters were the same (Ca + Mg carbonate, quartz, silicate and litter sodium chloride). The amounts of Ca + Mg carbonate showed a strong positive correlation with Dra and CU ( R 2 = 0.93 and 0.92), while the amounts of quartz showed a remarkable negative linear relationship with Dra and CU ( R 2 = 0.85 and 0.87). The main material responsible for emitter clogging was calcium carbonate deposits, which accounted for >88.1% of the total. Copyright © 2016 John Wiley & Sons, Ltd.